A Review of The Chord Progression and Presentation Format of The Song "Masih Ada" 2D Arranged By Oni and Friends - Budiyono, Abednego Ziposa Sabatnissan (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2023)
The song “Masih Ada” tells the story of someone who misses his lover, which is expressed through poetry and turned into a song. This research aims to (1) Analyze the Chord Progression of the song “Masih Ada” arranged by Oni and Friends. (2) Analyzing the Presentation Format of “Masih Ada” performed by Oni and Friends. The method used is descriptive qualitative analysis. The data used in this method is pure data obtained directly from Oni Krisnerwinto as the arranger. This research uses the research techniques of Observation, Interview, Documentation, and Literature Study. The findings show that Oni and Friends' arrangements provide a new interpretation, with the use of more complex and innovative chord progressions. Complex means that the chords and notes played are interconnected with the next chord. Innovative means changing the chord progression style with reharmonize. Based on the results of this research, it can be concluded that the chord progression used has many reharmonized changes. The presentation format used is a mixed large ensemble.